The Lovely Bones : A Novel - Sebold, Alice (London Picador, 2003)
After her murder, fourteen-year-old Susie discovers that life is not quite finished with her. From heaven, she watches her family and friends coping with her disappearance and her killer covering his tracks.
Keywords: Domestic fiction -- Murder victims' families -- Fiction